Analysis of Community Knowledge About DAGUSIBU Medicine In Sulaa Urban Village, Betoambari Sub-District - Annemelya Iftitah Sahupala; Yuyun Wirasasmita; Evi Mustiqawati (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: DAGUSIBU (Get, Use, Store, and Dispose Medicines Properly) is a public health program designed to improve community awareness and promote the rational management of medicines. Adequate knowledge of the correct procedures for obtaining, using, storing, and disposing of medicines is essential to ensure medication safety, effectiveness, and environmental protection. Objective: This study aimed to assess the level of public knowledge regarding DAGUSIBU among residents of Sulaa Village, Betoambari District. Methods: An observational study with a cross-sectional design was conducted among residents of Sulaa Village. Data were collected using a structured questionnaire distributed through Google Forms. Participants were selected using a purposive sampling technique. Data were analyzed descriptively and presented as percentages to determine the level of knowledge in each DAGUSIBU component. Results: The findings showed that respondents' knowledge regarding obtaining medicines (“Get Medicine”) was categorized as good, with a percentage score of 80.46%. Knowledge related to the proper use of medicines (“Use Medicine”) was categorized as sufficient, with a score of 70.69%. Similarly, knowledge regarding medicine storage (“Store Medicine”) was classified as sufficient, with a score of 73.48%. In contrast, knowledge concerning the proper disposal of medicines (“Dispose of Medicine”) was categorized as poor, with a score of 54.18%. Overall, the average level of public knowledge regarding DAGUSIBU was 69.70%, indicating a moderate or sufficient level of understanding. Conclusion: The overall level of public knowledge regarding DAGUSIBU among residents of Sulaa Village was categorized as sufficient. While knowledge related to obtaining medicines was relatively high, deficiencies were observed in knowledge regarding the proper disposal of medicines. Therefore, educational interventions and community-based health promotion programs are needed to improve public understanding and implementation of all aspects of DAGUSIBU, particularly medicine disposal practices. Keywords: DAGUSIBU; Knowledge; Medicine Management; Rational Drug Use; Community Awareness; Public Health.